Identification of a New Genetic Clade of Cowpea Mild Mottle Virus and Characterization of Its Interaction With Soybean Mosaic Virus in Co-infected Soybean - Wei, Zhongyan; Mao, Chenyang; Jiang, Chong; Zhang, Hehong; Chen, Jianping; Sun, Zongtao (Frontiers in Microbiology, 2021)
Cowpea mild mottle virus (CPMMV; genus Carlavirus) can be a destructive pathogen of soybean but there is little information about its distribution on soybean in China. Here, we collected soybean plants with virus-like symptoms from 11 fields widely scattered within China, and used high-throughput sequencing to determine their virome. Most samples (8/11) were co-infected by the well-studied potyvirus soybean mosaic virus (SMV) and CPMMV, and the remaining three samples were singly infected with CPMMV. The near-complete genome sequences of the 11 CPMMV isolates were determined and phylogenetic analysis showed that they constituted a new genetic clade. One recombination event was detected among the CPMMV sequences, and the isolate CPMMV_JL_CC was identified as recombinant. In mechanical inoculation assays, co-infection by CPMMV and SMV resulted in an enhancement of disease symptoms, but decreased the expression level of the genomic RNAs and CP of CPMMV, without significantly affecting SMV accumulation. The interaction between these viruses needs further investigation.